A review on the chemistry, coordination, structure and biological properties of 1-(acyl/aroyl)-3- (substituted) thioureas - Saeed, Aamer (2014)
This review provides an overview of the chemistry, structure and potential applications of 1- (acyl/aroyl)-3-(mono-substituted) and 1-(acyl/aroyl)-3,3-(di-substituted) thioureas, with general formula R1C(O)N(1)HC(S)N(3)R2R3. In recent years, the title compounds have found extensive applications as ligands in coordination chemistry. The effect that nitrogen substituents exert on the intra- and intermolecular hydrogen-bonding interactions is discussed, including their role on the coordination properties displayed by these ligands. Novel applications of transition metal complexes bearing 1-(acyl/aroyl)-3-(mono- and di-substituted) thioureas are introduced. Biological aspects are also highlighted. As recently demonstrated, high-throughput screening assay and structure–activity analyses are feasible for this class of compounds. The chemical versatility of 1-(acyl)-3-(substituted) thiourea molecules and the derived metal complexes, together with the possibility of determining detailed structural properties, join biological applications in a promising interdisciplinary approach. The bibliography includes 382 references with emphasis on the literature appearing after 2007.